2004
DOI: 10.1038/sj.onc.1207226
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of activated M-Ras in a murine mammary epithelial cell line induces epithelial–mesenchymal transition and tumorigenesis

Abstract: The expression of activated mutants of M-Ras (G22V or Q71L), but not wild-type M-Ras, in a murine mammary epithelial cell line, scp2, resulted in epithelial-mesenchymal transition (EMT) and oncogenic transformation. Cells expressing constitutively active M-Ras continued to grow in the absence of serum and exhibited a loss of the epithelial markers cytokeratin, E-cadherin and b-catenin, together with a gain of the mesenchymal marker vimentin, a loss of contact inhibition in monolayer growth and a gain of the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…30 Therefore, to investigate the effect of COX-2 expression on differentiation, we cultured the cells on Matrigel-coated plates, a method that has been used by other investigators to study epithelial differentiation. 23,24 Under these conditions, 10F-P and 10F-AS cells aggregated to form smooth spheroids (Fig. 4a), structures previously observed to form from well-differentiated mammary epithelial cells.…”
Section: Cox-2 Overexpression Inhibits Differentiationmentioning
confidence: 61%
See 2 more Smart Citations
“…30 Therefore, to investigate the effect of COX-2 expression on differentiation, we cultured the cells on Matrigel-coated plates, a method that has been used by other investigators to study epithelial differentiation. 23,24 Under these conditions, 10F-P and 10F-AS cells aggregated to form smooth spheroids (Fig. 4a), structures previously observed to form from well-differentiated mammary epithelial cells.…”
Section: Cox-2 Overexpression Inhibits Differentiationmentioning
confidence: 61%
“…4a), structures previously observed to form from well-differentiated mammary epithelial cells. 23,24 The 10F-S cells, however, formed irregular 3-dimensional structures with many fibroblast-like cells showing invasion into the Matrigel (Fig. 4b), suggesting differentiation of these cells was inhibited.…”
Section: Cox-2 Overexpression Inhibits Differentiationmentioning
confidence: 96%
See 1 more Smart Citation
“…16 It has been reported that in mammary epithelial cells another activated mutant member of the RAS subfamily, M-Ras, increased vimentin expression and resulted in EMT. 24 It appears that Ha-RASV12 has a higher transforming potential as opposed to its isoform Ki-RASV12. The unique gene expression profiles generated by each of the 2 RAS isoforms probably are responsible for these differences.…”
Section: Discussionmentioning
confidence: 99%
“…Activated forms of MRAS, such as the MRAS-G22V mutant which is constitutively in the GTP-bound form, mimic inducers (NGF or BMP2) and trigger neuronal or osteoblast differentiation in PC12 or C2C12 models, respectively (Kimmelman et al, 2002;Sun et al, 2006;WatanabeTakano et al, 2010), induce formation of peripheral microspikes in fibroblasts and participate in the reorganisation of the actin cytoskeleton (Matsumoto et al, 1997). In addition, these activated forms are oncogenic in murine mammary epithelial cell lines (Ward et al, 2004). MRAS function is potentially regulated by plexin B1, a dual-function GTPase-activating protein (GAP) for RRAS and MRAS, which remodels axon and dendrite morphology, respectively (Saito et al, 2009).…”
Section: Introductionmentioning
confidence: 99%